1999
DOI: 10.1111/j.1748-121x.1999.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

A reasonable woman standard in sexual harassment litigation

Abstract: Sexual harassment litigation may be thwarted by judges failing to address the acts in question from the perspective of the victim, thus legitimising behaviour acceptable to men but unacceptable to women. This paper shows how this problem may be overcome by adopting a 'reasonable woman ' standard to decide 8 (i) objectively, the acts in question constitute harassment; and (ii) subjectively, whether the victim suffered injury. Using US case law the paper shows how the reasonable woman standard, which has been ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…It also denies women a degree of protection in the workplace. These findings have a disturbing resonance with, and indeed replicate those of Monti (1999: 570), who analysed US cases of sexual harassment. Monti (1999) found that the victim's character was taken into account by the court, and that, as in many rape cases, judges put the women on trial for being unsociable and exposing themselves to harm for not trying to understand men.…”
Section: Evidential Difficulties Of Bringing Sexual Harassment Claisupporting
confidence: 75%
See 4 more Smart Citations
“…It also denies women a degree of protection in the workplace. These findings have a disturbing resonance with, and indeed replicate those of Monti (1999: 570), who analysed US cases of sexual harassment. Monti (1999) found that the victim's character was taken into account by the court, and that, as in many rape cases, judges put the women on trial for being unsociable and exposing themselves to harm for not trying to understand men.…”
Section: Evidential Difficulties Of Bringing Sexual Harassment Claisupporting
confidence: 75%
“…Existing research strongly indicates that most women experiencing sexual harassment in organisations react passively, in the main trying to ignore the behaviour and/or avoid the perpetrator (Conaghan, 2002; Monti, 1999; Samuels, 2004). This dominant reaction has been understood by researchers as reflecting the realities of power differentials in organisations, and how these operate through sexual harassment.…”
Section: Applicants' Reactions To Suffering Sexual Harassment and Amentioning
confidence: 99%
See 3 more Smart Citations